Measurement of electroweak production of two jets in association with a Z boson in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2015)
The purely electroweak (EW) cross section for the production of two jets in association with a Z boson, in proton-proton collisions at root s = 8 TeV, is measured using data recorded by the CMS experiment at the CERN LHC, corresponding to an integrated luminosity of 19.7 fb(-1). The electroweak cross section for the lljj final state (with l = e or mu and j representing the quarks produced in the hard interaction) in the kinematic region defined by M-ll > 50 GeV, M-jj > 120 GeV, transverse momentum p(Tj) > 25 GeV, and pseudorapidity vertical bar eta(j)vertical bar < 5, is found to be sigma(EW) (lljj) = 174 +/- 15 (stat) +/- 40 (syst) fb, in agreement with the standard model prediction. The associated jet activity of the selected events is studied, in particular in a signal-enriched region of phase space, and the measurements are found to be in agreement with QCD predictions.
Keywords: RAPIDITY GAPS